Strengthening TB Infection Control and Its Impact on TB Screening Practices Among Healthcare Workers During The COVID-19 Pandemic in Zimbabwe - Mashamba Alethea; Pepukai Mildred; Muzambi Margaret; Gwayagwaya Chipo; Maruta Anna; Mandisarisa John; Date Anand; A. Maloney Susan; Forno Rodriguez Diana; Ershova Julia; Robertson1 Valerie (International Journal of Infection Prevention, 2026)
Introduction The risk of exposure to M. tuberculosis among healthcare workers (HCW) remains a public health concern worldwide. During the COVID-19 pandemic, the Biomedical Research and Training Institute supported the Zimbabwe Ministry of Health and Child Care in strengthening infection prevention and control (IPC) practices in healthcare facilities (HCF), integrating tuberculosis (TB) infection control (TBIC) into the intervention strategy. We describe the impact of this intervention on TBIC practices and HCW screening outcomes. Methods The strategy, implemented from June 2021–September 2022, included IPC mentorship training, competency assessments, and use of a standardized risk assessment tool for progress monitoring. For the training purposes, the project developed eight practical problem-solving IPC modules including an occupational health component. Trained mentors conducted bi-monthly site support visits (SSV), used a checklist to track compliance, and assessed competencies of HCW at the targeted facilities. Facility-based risk assessments were conducted three times during the project implementation. Results During the intervention, 1,865 HCW from 105 facilities were trained. Availability and use of personal protective equipment improved by 49% and 42%, respectively. The proportion of HCF with designated areas for sputum collection increased by 43%. The proportion of HCF that screened HCW for TB increased by 42% with 3,761 HCW screened during the project period. Fourteen were diagnosed with TB and referred for care, resulting in 372 new cases per 100,000. Conclusion The implemented strategy of training, mentorship, and regular SSV strengthened TBIC measures, improved TB screening practices and case finding among HCW. Improving and maintaining practices is critical for effective TBIC.
Keywords: Zimbabwe